Pamirian crossroads and beyond human geography and geopolitics - Kreutzmann, Hermann 1955- (Brill, 2024)
"In Pamirian Crossroads and Beyond Hermann Kreutzmann offers insights in his fieldwork-based research in High Asia during four decades. A human-geographical perspective is pursued in which case studies about colonial and post-colonial boundary-making, exchange relations of mountain communities across international borders, the transformation of agricultural and pastoral practices and the effects of modernisation strategies in neighbouring counties are centred in the Hindukush, Wakhan Quadrangle, Pamirian Crossroads, Karakoram Mountains and Himalaya. Empirical evidence is augmented by in-depth archival research, thus allowing a perspective from the 19th to the 21st century. By shifting the focus to mountain peripheries and emphasising spaces in between urban centres of power in Afghanistan, Pakistan, China, and the Central Asian Republics different arenas of confrontation and effective changes emerge"--
Auf der Rückseite des Titelblattes: "The chapters in this book are a collection of works by Dr. Kreutzmann, originally published between 1998 and 2022. Each chapter concludes with a reference to the original publication."
Keywords: Human geography / Asia, Central; Geopolitics / Asia, Central; Borderlands / Asia, Central; Mountain people / Asia, Central; Aufsatzsammlung